The chromatin remodeler ISWI regulates the cellular response to hypoxia: role of FIH - Melvin, Andrew (The American Society for Cell Biology, 2011)
The hypoxia-inducible factor (HIF) is a master regulator of the cellular response to hypoxia. Its levels and activity are controlled by dioxygenases called prolyl-hydroxylases and factor inhibiting HIF (FIH). To activate genes, HIF has to access sequences in DNA that are integrated in chromatin. It is known that the chromatin-remodeling complex switch/sucrose nonfermentable (SWI/SNF) is essential for HIF activity. However, no additional information exists about the role of other chromatin-remodeling enzymes in hypoxia. Here we describe the role of imitation switch (ISWI) in the cellular response to hypoxia. We find that unlike SWI/SNF, ISWI depletion enhances HIF activity without altering its levels. Furthermore, ISWI knockdown only alters a subset of HIF target genes. Mechanistically, we find that ISWI is required for full expression of FIH mRNA and protein levels by changing RNA polymerase II loading to the FIH promoter. Of interest, exogenous FIH can rescue the ISWI-mediated upregulation of CA9 but not BNIP3, suggesting that FIH-independent mechanisms are also involved. Of importance, ISWI depletion alters the cellular response to hypoxia by reducing autophagy and increasing apoptosis. These results demonstrate a novel role for ISWI as a survival factor during the cellular response to hypoxia.